Band-structure effects in photoelectron-emission spectra from metal surfaces - Rios Rubiano, Carlos Alberto (2012)
Photoelectron emission from the valence band of a metal surface due to the grazing incidence of ultrashort laser pulses is studied in the framework of a distorted-wave formulation. We propose a model, named the band-structure-based–Volkov (BSB-V) approximation, which takes into account the contribution of the band structure of the solid. The BSB-V approach is applied to calculate differential electron-emission probabilities for Al(111) and Be(0001) surfaces. A noticeable inﬂuence of the electronic band structure was observed in the case of beryllium, while for aluminum such effects were found to play a minor role.